Accelerating rural energy access for agricultural transformation: contribution of the CGIAR Research Program on Water, Land and Ecosystems to transforming food, land and water systems in a climate crisis - Magalhaes, Marilia; Ringler, Claudia; Verma, Shilp; Schmitter, Petra S. (International Water Management Institute, 2021)
With adverse impacts of climate change growing in number and intensity, there is an urgent need to reduce emissions from food systems to net zero. This can only be achieved if rural areas in low- and middle-income countries gain access to clean energy. A review of the research and capacity building contributions of the CGIAR Research Program on Water, Land and Ecosystems (WLE) over the last 10 years suggests important contributions in the areas of energy policy and energy investment planning, cost and feasibility frameworks, and business models for clean energy technology uptake. WLE has also conducted successful pilot projects on solar irrigation to provide an evidence base for scaling up innovative energy initiatives. Finally, the program also considered non-agricultural uses of energy where relevant to food systems, and implemented capacity building activities. Going forward, CGIAR has a key role to play in providing information, supporting access and piloting innovative, scalable clean energy interventions to support the achievement of multiple impacts for the poorest and most food-insecure women and men farmers and entrepreneurs.